A Conceptual Model of Religious Character Transformation through Islamic Religious Education: A Systematic Literature Review - muhammad azka; tumin tumin (Institut Agama Islam An-Nawawi Purworejo, 2026)
The rapid development of twenty-first-century society requires Islamic Religious Education (IRE) to function not only as a medium for transmitting religious knowledge but also as an instrument for religious character transformation. This study aims to synthesize the literature on religious character transformation through Islamic Religious Education and to develop a conceptual model relevant to contemporary educational challenges. A Systematic Literature Review (SLR) following the PRISMA 2020 guidelines was conducted using the Scopus database. Of the 344 articles initially identified, 32 met the inclusion criteria, and 30 full-text studies that satisfied the methodological quality appraisal were synthesized using thematic synthesis. The findings identified six interrelated dimensions of religious character transformation: religious identity, morality and religiosity, tolerance and multiculturalism, citizenship education and social responsibility, transformational pedagogy, and ecological awareness. Based on these findings, this study proposes a conceptual model that integrates these dimensions into a unified framework for understanding religious character transformation through Islamic Religious Education. The proposed model provides a theoretical foundation for future empirical research and supports the development of more transformative, inclusive, and contextually responsive Islamic Religious Education.